Terrestrial nematodes from the Maritime Antarctic - Milka Elshishka; Aleksandar Mladenov; Stela Lazarova; Vlada Peneva (Biodiversity Data Journal, 2023)
Soil nematodes are one of the most important terrestrial faunal groups in Antarctica, as they are a major component of soil micro-food webs. Despite their crucial role in soil processes, knowledge of their species diversity and distribution is still incomplete. Taxonomic studies of Antarctic nematodes are fragmented, which prevents assessment of the degree of endemicity and distribution of the species, as well as other aspects of biogeography.The present study is focused on the nematode fauna of one of the three Antarctic sub-regions, the Maritime Antarctic and summarises all findings published up to April 2023. A species list that includes 44 species, belonging to 21 genera, 16 families and eight orders is provided. A review of the literature on terrestrial nematodes inhabiting the Maritime Antarctic showed that the sites are unevenly studied. Three islands (Signy, King George and Livingston Islands) revealed highest species richness, probably due to the highest rates of research effort. Most species and four genera (Antarctenchus, Pararhyssocolpus, Amblydorylaimus and Enchodeloides) are endemic, proving that nematode fauna of the Maritime Antarctic is autochthonous and unique. Several groups of islands/sites have been revealed, based on their nematode fauna. The study showed that species with a limited distribution prevailed, while only two species (Plectus antarcticus and Coomansus gerlachei) have been found in more than 50% of the sites. Based on the literature data, details on species localities, microhabitat distribution, plant associations and availability of DNA sequences are provided.